To Prison, With Mom: International Due Process Issues for Children and Mothers Posed by Prison Nurseries - Johnson-Gomez, Alexa; Matonich, Julie (Columbia Journal of Gender and Law, 2025)
Some jurisdictions automatically permit infants born in custody to stay with their mothers, while others enforce immediate separation. Both practices contradict the United Nations Convention on the Rights of the Child’s best interests standard and violate general notions of due process. By comparing automatic actions in Mexico, India, and Canada with the United Kingdom’s multi-agency admissions boards and Australia’s Living with Mum Program, this Article demonstrates how transparent, case-by-case decision-making upholds the human rights of both mother and child. We recommend that each case be thoroughly assessed by an interdisciplinary team to ensure the child’s voice is heard and their best interests are prioritized. Decision-makers must weigh the risks and benefits of placing a child in prison with a parent, considering factors such as the child’s age, maturity, and the conditions of both the prison and alternative placements. The decision-making process should be transparent, with written findings and an opportunity for judicial review. Meanwhile, governments must systematically collect data and support longitudinal research to ensure policies truly prioritize the human rights of both mother and child.